Pharmaceutical Nanotechnology: Blended Nanoparticle System Based on Miscible Structurally Similar Polymers: A Safe, Simple, Targeted, and Surprisingly High Efficiency Vehicle for Cancer Therapy (Adv. Healthcare Mater. 8/2015). Issue 8 (3rd June 2015) - Tao, Wei; Zhang, Jinxie; Zeng, Xiaowei; Liu, Danny; Liu, Gan; Zhu, Xi; Liu, Yanlan; Yu, Qingtong; Huang, Laiqiang; Mei, Lin
<x xml:space="preserve">Abstract</x> On page 1203, a novel blended nanoparticle (NP) system for the delivery of anticancer drugs and its surprisingly high efficacy for cancer chemotherapy by blending a targeting polymer folic acid‐poly(ethylene glycol)‐b‐poly(lactide‐co‐glycolide) (FA‐PEG‐b‐PLGA) and a miscible structurally similar polymer D‐α‐tocopheryl polyethylene glycol 1000 succinate‐poly(lactide‐co‐glycolide) (TPGS‐PLGA) are reported by X. Zeng, L. Huang, L. Mei, and colleagues. This blended NP system can be achieved through a simple and effective nanoprecipitation technique, possessing unique properties.